1991
DOI: 10.1055/s-2007-1020002
|View full text |Cite
|
Sign up to set email alerts
|

Eversion Endarteriectomy of the Internal Carotid Artery

Abstract: Eversion endarteriectomy has been proposed as a reliable and rapid method for operating on an ulcerated or stenosed internal carotid artery. The surgical technique is presented in detail. The perioperative course is appraised in a series of 60 operations. Irrespective of age and other diseases in the patients and the preoperative state of the ipsilateral and contralateral vessels, a perioperative morbidity of 1.6% (a temporary neurological deficit) and no lethal outcomes were found. Indication for operation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, many authors have reported an improvement in their outcome after standard CEA when they started resecting all kinks, or shortening or transversely folding all elongated ICAs. 21,25,30,31 CEE is a rapid surgical procedure. The carotid crossclamping (P ϭ .01), hemostasis (P ϭ .005), and overall surgical (P ϭ .01) times are significantly lower than for CEAP.…”
Section: Discussionmentioning
confidence: 99%
“…However, many authors have reported an improvement in their outcome after standard CEA when they started resecting all kinks, or shortening or transversely folding all elongated ICAs. 21,25,30,31 CEE is a rapid surgical procedure. The carotid crossclamping (P ϭ .01), hemostasis (P ϭ .005), and overall surgical (P ϭ .01) times are significantly lower than for CEAP.…”
Section: Discussionmentioning
confidence: 99%
“…Bosse et al employed this technique in 60 procedures with no permanent neurologic deficits or mortality. 16 Berguer reported a series of 100 consecutive patients undergoing eversion endarterectomy with division of the ICA at the bifurcation (Type 1) or of the CCA (Type 2) with no perioperative stroke or operative mortality.&dquo; Mean follow-up was 14 mos in this series with no late restenosis reported. Koskas et al performed 168 eversion procedures with a 4.8% stroke/mortality rate .22 Mean follow-up in this series was 62 mos with patency determined by either duplex scan or arteriography at yearly intervals.…”
Section: Discussionmentioning
confidence: 97%
“…Reported symptomatic or asymptomatic restenosis rates range from 2% to 30%, but the cause of restenosis remains unknown.6-11 Once complete removal of the plaque is obtained, the restenosis may be due to recurrence of disease, neo-intimal hyperplasia or technical problems related to closure, therefore, there is support for patch angioplasty closure to prevent distal narrowing of the internal carotid artery (ICA)Y- 14 Recently, some European and North American centers have shown that eversion endarterectomy of the ICA, an alternate technique that avoids a suture line in the distal ICA, may reduce early occlusion and restenosis rates. [15][16][17][18][19][20][21][22][23][24] We have adopted this technique since 1993, and have performed eversion endarterectomy of the ICA in over 1,500 cases. In this chapter we present technical details, some limitations and our cumulative results using this technique.…”
mentioning
confidence: 99%
“…[24][25][26][27][28][29][30] The eversion technique enjoys the potential advantages of requiring less time in the operating room because of a shorter suture line as well as not requiring the implantation of a prosthetic, homograft, or vein patch, which requires an incision in the leg to obtain autologous saphenous vein. Prosthetic or homograft patches have additional associated cost and might be more susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%